2018
DOI: 10.1111/ejn.13937
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the right temporo‐parietal and premotor cortices in self‐location and body ownership

Abstract: In the rubber hand illusion (RHI), the feeling that a fake hand belongs to oneself can be induced by the simultaneous, congruent touch of the fake visible hand and one's own hidden hand. This condition is also associated with a recalibration of the perceived location of the real hand. A cortical network, including premotor and temporo-parietal areas, has been proposed as the basis of the RHI. However, the causal contribution of these areas to the discrete illusory components remains unclear. We used transcrani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…Our data suggest that transcranial stimulation affected the experience of ownership during both the illusion and control conditions, suggestive of a broad effect of stimulation that is not dependent on synchronous visuotactile feedback. This is in line with two recent neurostimulation studies reporting mainly non-illusion-specific effects of anodal stimulation over right PPC ( Convento et al, 2018;Lira et al, 2018).…”
Section: Neurostimulation Modulates Limb Disownershipsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data suggest that transcranial stimulation affected the experience of ownership during both the illusion and control conditions, suggestive of a broad effect of stimulation that is not dependent on synchronous visuotactile feedback. This is in line with two recent neurostimulation studies reporting mainly non-illusion-specific effects of anodal stimulation over right PPC ( Convento et al, 2018;Lira et al, 2018).…”
Section: Neurostimulation Modulates Limb Disownershipsupporting
confidence: 92%
“…In line with previous literature we expected stimulation of right parietal networks to modulate body ownership. This hypothesis is further supported by two recent tDCS studies reporting a modulation of the drift measure of the RHI in case of anodal stimulation applied over the right temporo-parietal junction (and right premotor cortex (Convento et al, 2018) and a change in the onset time of the illusion, but not drift, during anodal stimulation over right posterior parietal cortex (PPC) respectively (Lira et al, 2018). These studies further reported significant, if slightly different, effects of anodal tDCS on perceived body ownership.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, a recent study (Daltrozzo, Kotchoubey, Gueler, & Karim, ) showed an abnormal body perception (ABP) after inhibitory rTMS over rTPJ in 65% of their participants, but an ABP was reported also under inhibitory rTMS at the control site, supporting the idea that rTPJ may not play a specific role in this process. More recently, a different brain stimulation technique, such as transcranial direct current stimulation (tDCS), was used to assess the contribution of the right premotor cortex (rPMC) and the rTPJ to the RHI (Convento, Romano, Maravita, & Bolognini, ). In this study, the anodal tDCS on both rPMC and rTPJ increased the Proprioceptive Drift, even if the difference between synchronous and asynchronous condition was minimized when tDCS was applied over the rPMC, while it was amplified when the rTPJ was targeted.…”
Section: Discussionmentioning
confidence: 99%
“…Embodiment of a fake limb cannot be increased with non-invasive brain stimulation techniques due to a possible ceiling effect. However, the recent reports of a slight increase of proprioceptive drift and subjective experience of body ownership with transcranial direct current stimulation ( Convento et al, 2018 ; Lira et al, 2018 ) may suggest that iTBS could be not the better suited neuromodulating protocol for this purpose. iTBS was chosen because it is short and effective, but differences in the individual network sensitivity to the magnetic pulse ( Hamada et al, 2012 ) and in individual functional connectivity ( Nettekoven et al, 2015 ) make iTBS efficacy highly variable across subjects and, especially, across brain regions other than primary motor cortex ( Suppa et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%